PENGARUH RASIO UTANG, PERTUMBUHAN ASET, LABA BERSIH, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI TAMBANG DI INDONESIA - Muhammad Andrei Lesmono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The progress of a company cannot be separated from the assessment of the shareholders, in this case the company's ability to provide benefits. In other words, company value reflects the performance and business growth of a company. It explicitly means that the business that is carried out is profitable, then has an impact on increasing assets and market growth, and has an impact on increasing the welfare of shareholders. This study aims to analyze the determinants of firm value based on the aspects of assets, capital and profits. The phenomenon was studied based on a quantitative perspective with panel data regression analysis. The research object is mining companies in Indonesia with a purposive sampling technique. The results of the study explain that changes in asset structure (size and asset growth) in a positive direction strengthen firm value. In addition, the strengthening of capital over debt strengthens the effect of profit on share prices (firm value). This condition confirms that mining companies in Indonesia have good prospects in terms of profits, assets and capital, so investors deserve to be assessed well.